Inovasi Edukasi Lingkungan melalui Pemanfaatan Minyak Jelantah Menjadi Lilin di SD Desa Mabar - Pada Mulia Raja; Ritna Wahyuna; Mahyunis Mahyunis; Zakwan Zakwan; Rafael Remit Winardi Winardi; William William (CV. IRA PUBLISHING, 2025)
Used cooking oil is a household waste that can pollute the environment if disposed of improperly. In Mabar Village, Bangun Purba District, public awareness of waste oil management remains low. This community service program aims to provide environmental education for elementary school students by introducing the utilization of used cooking oil to produce candles. The program involved 21 students from grades 4–5. The methods included socialization on the dangers of used oil, hands-on candle-making practice, and evaluation using pre- and post-tests. The results show a significant improvement in students’ understanding, rising from 20% on the pre-test to 85% on the post-test. Furthermore, all participants successfully produced candles independently. This program effectively enhances children’s knowledge and environmental awareness.